DC transport critical current measurements on high temperature superconductors in pulsed fields up to 50T - Ryan, D; Hole, C; vanderBurgt, M; Jones, H; Davies, C; Grovenor, C; Goringe, M; DewHughes, D (1996)
With a view to the long term exploitation of the high upper critical fields of high temperature and Chevrel phase superconductors and their use in very high field superconducting magnets, we are making measurements of critical currents on practical versions of these superconductors in very high pulsed magnetic fields; up to 50 T so far, The measurements are made using transport currents in order to simulate, as far as possible, conditions in a magnet, We compare the results with those taken in the highest steady fields available to us; 18 T at present, In this paper we present our latest results and describe how the technique is developing. We also review our attempts to model the mechanisms which give rise to the characteristic function of V(dB/dt) which we observe.